1988
DOI: 10.1136/hrt.59.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Vasculitis complicating treatment with intravenous anisoylated plasminogen streptokinase activator complex in acute myocardial infarction.

Abstract: In six patients (five male, one female) a purpuric rash developed 7-15 days after the administration of anisoylated plasminogen streptokinase activator complex. In each case there was purpura, particularly of the extensor surfaces of the legs. In two patients the rash also affected the extensor surfaces of their arms. The lesions varied from areas of purpura (3-7 mm in diameter) to necrotic vesicles (figure). The rash began to resolve after 2-5 days and had completely disappeared after three weeks. The table g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Antibodies to SK arise naturally following exposure to bacteria of the genus streptococcus and are present in virtually all individuals tested (43). Therapeutic administration of SKcontaining thrombolytics leads to an anamnestic response with increased production of antibodies, decreased rates of thrombolysis, and subsequent immunologic complications such as anaphylaxis, vasculitis or serum sickness in some treated patients (28)(29)(30)(31)(32)(33)(34). Because t-PA is a naturally occurring human protein, it should not be immunogenic in humans.…”
Section: Patients Rabbit Baboon Marmosetmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibodies to SK arise naturally following exposure to bacteria of the genus streptococcus and are present in virtually all individuals tested (43). Therapeutic administration of SKcontaining thrombolytics leads to an anamnestic response with increased production of antibodies, decreased rates of thrombolysis, and subsequent immunologic complications such as anaphylaxis, vasculitis or serum sickness in some treated patients (28)(29)(30)(31)(32)(33)(34). Because t-PA is a naturally occurring human protein, it should not be immunogenic in humans.…”
Section: Patients Rabbit Baboon Marmosetmentioning
confidence: 99%
“…The effects of these antibodies may be completely benign, or they may lead to the neutralization of the drug's biological activity or to toxicity due to immune complex formation. In particular, in the field of thrombolytic therapy, preexisting antibodies to the bacterial protein streptokinase (SK) have resulted in decreased rates of thrombolysis (24)(25)(26)(27), immune complex disease (28)(29)(30)(31) or anaphylaxis (31)(32)(33)(34) in patients treated with SK or its derivative, anisoylated plasminogen SK activator complex. Therefore, in spite of the fact that rt-PA is a highly purified glycoprotein, identical in primary structure to the human protein (35), sera from rt-PA treated patients were tested for the presence of antibodies to t-PA.…”
Section: Introductionmentioning
confidence: 99%
“…4 Vasculitis has also been reported after treatment with anistreplase. 25 Readministration of plasminogen activators such as tissue plasminogen activator and urokinase, which are non-allergenic, is less likely to reduce efficacy and cause allergic reactions. Little is known of the risks of readministration of these agents, however, particularly of haemorrhage during the first few days after initial treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Immediate reactions include bronchospasm, urticaria, and anaphylaxis 1. Delayed reactions include vasculitis and an illness like serum sickness 2 3. Kinshuk suggested that iritis may be associated with streptokinase treatment 4.…”
mentioning
confidence: 99%